Anti-EpCAM functionalized graphene oxide vector for tumor targeted siRNA delivery and cancer therapy - Si Chen (Elsevier, 2021)
Graphene oxide (GO) has emerged as a potential drug delivery vector. For siRNA delivery, GO should be modified to endow it with gene delivery ability and targeting effect. However, the cationic materials used previously usually had greater toxicity. In this study, GO was modified with a non-toxicity cationic material (chitosan) and a tumor specific monoclonal antibody (anti-EpCAM) for the delivery of survivin-siRNA (GCE/siRNA). And the vector (GCE) prepared was proved with excellent biosafety and tumor targeting effect. The GCE exhibited superior performance in loading siRNA, maintained stability in different solutions and showed excellent protection effect for survivin-siRNA in vitro. The gene silencing results in vitro showed that the mRNA level and protein level were down-regulated by 48.24% ± 2.50% and 44.12% ± 3.03%, respectively, which was equal with positive control (P > 0.05). It was also demonstrated that GCE/siRNA had a strong antitumor effect in vitro, which was attributed to the efficient antiproliferation, and migration and invasion inhibition effect of GCE/siRNA. The results in vivo indicated that GCE could accumulate siRNA in tumor tissues. The tumor inhibition rate of GCE/siRNA 54.74% ± 5.51% was significantly higher than control 4.87% ± 8.49%. Moreover, GCE/siRNA showed no toxicity for blood and main organs, suggesting that it is a biosafety carrier for gene delivery. Taken together, this study provides a novel design strategy for gene delivery system and siRNA formulation.